ISLAM DAN AKHLAK : LANDASAN PEMBENTUKAN KARAKTER MUSLIM DALAM KEHIDUPAN SEHARI-HARI - Mutmainnah; Muthiyah Salsabilah; Abbas; Dahlan Lama Bawa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Islam is a religion that governs all aspects of human life, including relationships with Allah SWT and relationships with other human beings. One of the core teachings of Islam is the formation of noble morals as the foundation of individual and social life. This article aims to examine the concepts of Islam and morals, their relationship, the types of morals in Islam, the sources of morals, and their implementation in daily life. The writing method used is a literature study by examining the Quran, hadith, and relevant scientific literature. The results of the study indicate that morals are a concrete manifestation of faith and serve as a benchmark for the quality of a person's Islam. The consistent implementation of Islamic morals can shape the character of a faithful, knowledgeable, and responsible Muslim who is able to face the challenges of modern life.